Estimates of the variance components, heritability and genetic gains of phenotypic traits in citron watermelon (Citrullus lanatus var. citroides). (6th August 2021) - Ngwepe, Mantlo Richard; Shimelis, Hussein; Mashilo, Jacob
Abstract: The present study estimated variance components, heritability and genetic advance of phenotypic traits in citron watermelon to guide selection of superior genotypes for direct production and breeding. Thirty‐six citron watermelon landrace accessions were evaluated across two seasons using a 6 × 6 alpha lattice design with three replications. High broad‐sense heritability and genetic advance as per cent of the mean were recorded for fruit length at 83.86% and 4730.45%, seed length (77.73% and 1731.27%), hundred seed weight (73.73% and 4027.36%), fruit diameter (70.44% and 2949.64%) and fruit weight (70.39% and 8490.05%), respectively. Step‐wise regression analysis revealed marketable fruit yield (Myld) and total number of fruits per plant (TNFr) explained 89% ( R 2 = .89) of total variation for total fruit yield per plant (TFYld), whereas number of seed per fruit (NSPFr) and hundred seed weight (HSW) explained 92% ( R 2 = .92) of total variation for seed yield per fruit (SYPFr). Citron watermelon landrace accessions WWM03, WWM14, WWM16, WWM39, WWM65, WWM67 and WWM79 with high TFYld and SYPFr were selected for production or breeding.